Inclusive education of children with disabilities in the context of the rural schools - Erbyagina A. A. (Interactive science, 2016)
the paper describes the conditions of inclusive education in rural ungraded school. The problems of implementing inclusive education in the rural school are also discussed.
Keywords: инклюзивное образование; inclusive education; экспериментальная площадка; доступное образование; accessible education; experimental playground